Dyes in History and Archaeology 41 - Hacke, Marei; Norrehed, Sara; Dyer, Joanne; Kirby, Jo; Gaibor, Art Proaño; Degano, Ilaria; Koren, Zvi; Sandström, Edith (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint features contributions from the conference DHA41. Dyes in History and Archaeology (DHA) is an annual international conference that focuses on the academic discussion of dyes and organic pigments which have been used in the past. Every year since 1982, this meeting has drawn together conservators; curators; (technical) art historians; craftspeople; artists; independent scholars; and scientists and academics from museums, universities, research centers, and other public or private institutions. Their common interest is to delve deeply into the history, production, application, and properties of organic colorants, as well as their analytical characterization and identification, often in textile objects, but also in other substrates as well as painted surfaces. In the autumn of 2022, the 41st DHA conference was hosted by the Swedish National Heritage Board in Visby. The abstracts are published on the DiVA portal (Digitala Vetenskapliga Arkivet), and many of the presented posters are available for download from the conference program. We are very grateful to the authors of the following 16 articles for submitting their manuscripts and allowing us to put together a publication that presents the fascinating breadth of research into Dyes in History and Archaeology.